2020
DOI: 10.3390/cancers12061549
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis of Key Differentially Expressed Genes Identifies DBN1 as a Predictive Marker of Response to Endocrine Therapy in Luminal Breast Cancer

Abstract: Endocrine therapy is the mainstay of adjuvant treatment for patients with luminal breast cancer. Despite ongoing advances in endocrine therapy to date, a proportion of patients ultimately develop endocrine resistance, resulting in failure of therapy and poor prognosis. Therefore, as part of the growing concept of personalised medicine, the need for identification of predictive markers of endocrine therapy response at an early stage, is recognised. The METABRIC series was used to identify differentially express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…KIF2C 43 induces proliferation, migration, and invasion in gastric cancer patients through the MAPK signaling pathway. Drebrin 1 ( DBN1 ) 44 has been reported to be expressed in breast cancer. MAP1B 45 has been reported to be associated with lung cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…KIF2C 43 induces proliferation, migration, and invasion in gastric cancer patients through the MAPK signaling pathway. Drebrin 1 ( DBN1 ) 44 has been reported to be expressed in breast cancer. MAP1B 45 has been reported to be associated with lung cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors used immunohistochemical techniques to measure the overexpression of DBN1 in colorectal cancer tissue lymph nodes and liver metastases in matching tissue sections [ 41 ]. Also, DBN1 is an independent prognostic indicator for luminal breast cancer related to endocrine treatment response and prognosis [ 42 ]. Lyama et al found that, in terms of disease-free survival rate, the prognosis of patients with lung adenocarcinoma with strong DBN1 expression was significantly worse than that of patients with weak DBN1 expression [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of risk factors, DBN1 is an actin-binding protein, which acts as a ferroptosis regulator in pancreatic cancer ( 32 ). High DBN1 expression has been reported to be significantly associated with a poorer prognosis and drug resistance in various types of cancer ( 59 ), including lung adenocarcinoma and breast cancer. Elevated HES1 expression has also been previously reported in multiple types of cancer, including ovarian cancer ( 60 ), non-small cell lung cancer ( 61 ) and breast cancer ( 62 ).…”
Section: Discussionmentioning
confidence: 99%